Comparative serum biochemical and inflammatory profiles between repeat breeder and normal cyclic Holstein Friesian crossbred cows in Bangladesh - Hasan, Md. Mehedi; Islam, Md. Rashedul; Hafsa Hossain; Maksuda Taslima; Hamid, Sm. Ahasanul; Tuser, Mozahidul Islam; Juli, Nurjahan Akter; Al Wasef; Mahfuzul Islam; Jahan, Mst. Sharifa (Universitas Airlangga, 2026)
Repeat breeding syndrome (RBS) has adverse effects on dairy profitability in Bangladesh. This study compared serum biochemical profiles between RBS-affected and normal cyclic Holstein Friesian crossbred cows to identify potential metabolic biomarkers. A total of thirty-two lactating cows (3-8 years old, body condition score 2.5-4.0/5) were categorized into repeat breeders (RB, n= 16; ≥3 failed artificial inseminations with normal estrus) and normal cyclic controls (NC, n= 16; matched for age, parity, and postpartum status). Serum samples were analyzed for minerals (Ca, P, Mg), proteins (total protein, albumin, blood urea nitrogen [BUN], C-reactive protein [CRP]), and metabolites (glucose, cholesterol, bilirubin) using commercial diagnostic kits (Span Diagnostics). Repeat breeder cows required significantly more services per conception (4.2 ± 2.1 vs. 0.6 ± 0.7; p <0.001) and exhibited hypoglycemia (74.5 ± 8.4 vs 94.0 ± 4.3 mg/dL; p= 0.002), lower bilirubin levels (<1 mg/dL; 0.0 ± 0.0 vs 0.09 ± 0.03 mg/dL; p= 0.002) indicating enhanced hepatic clearance, elevated BUN (23.8 ± 3.6 vs 20.9 ± 1.9 mg/dL; p <0.05), and increased CRP concentrations (2.0 ± 0.7 vs 1.7 ± 0.4 mg/dL; p= 0.042). These biochemical alterations indicate a negative energy balance and subclinical inflammation, which are likely important etiological factors contributing to RBS in tropical dairy cows. The findings suggest that metabolic correction strategies may improve fertility, although further validation is required.